Pengaruh Gegar Budaya Terhadap Interaksi Sosial dan Penyesuian Diri Mahasiswa Perantau Program Studi Bimbingan dan Konseling - Permatasari, Devi; Sari, Eva Kartika Wulan (JKI (Jurnal Konseling Indonesia), 2023)
The study aims to describe the level of culture shock, sosial interaction and self-adjustment experienced by overseas students of the Guidance and Counseling study program at PGRI Kanjuruhan University Malang, examine the effect of culture shock on sosial interaction of overseas students, and examine the effect of culture shock on self-adjustment of overseas students. This research uses descriptive correlation quantitative method. The research population was 143 guidance and counseling students from class 2020 to 2022. The research sample was 33 overseas students from outside Java, taken with simple random sampling technique. The instruments used were the Culture Shock Scale developed by researchers with a reliability of 0.798 and the Sosial Interaction Scale developed by researchers with a reliability of 0.734, and the Self-Adjustment Scale developed by researchers with a reliability of 0.726. The conclusion of this study is that there is an influence of culture shock on the sosial interaction of overseas students, and there is an influence of culture shock on the self-adjustment of overseas students.